Culinary Lifestyle and Consumer Culture in Consuming Gacoan Noodles in Yogyakarta Students through the Perspective of Jean Baudrillard's Consumerism Theory - Chrissendy, Daniel; Narwaya, Tri Guntur; Febrianty, Yeni (Asian Journal of Management Analytics, 2025)
This thesis examines the culinary lifestyle and consumer culture of Yogyakarta students in consuming Mie Gacoan through the perspective of Jean Baudrillard's theory of consumerism. The study aims to analyze how the culinary lifestyle and consumer culture of students are formed in the context of Mie Gacoan consumption. Using a qualitative descriptive method with a postmodern paradigm, data were collected through interviews, non-participatory observations, and documentation of Yogyakarta students who regularly consume Mie Gacoan. Data analysis employs Baudrillard's theory of consumerism, which views consumption as a process of identity and social status formation. The research findings indicate that the consumption of Mie Gacoan among Yogyakarta students is not solely based on physiological needs but is also influenced by lifestyle, consumer culture, social media, and the desire to build certain identities and social statuses. The study concludes that food consumption is a complex social phenomenon where food choices become symbols of status, identity, and social capital.